Floristic Diversity along Altitudinal Gradient in Shopian Forest Range of J. & K., India - Mugloo, Javeed A.; Adil, Mir; Pala, Nazir A.; Rashid, Megna (Indian Forester, 2021)
The present study was carried out in the Shopian Forest Range in Kashmir Valley of Jammu and Kashmir, Union Territory of India. The study area was divided into three altitudinal gradients (1800m-2100m; 2100-2400m; 2400- 2700m) and stratified random sampling technique was used to study the community composition and phyto-sociological parameters of the vegetation. A total of 53 plant species belonging to 35 families were reported including 09 trees, 08 shrubs and 36 herbs. Poaceae was the dominant family represented by seven species, followed by Pinaceae, Rosaceae and Fabaceae with four species each. The presence of six trees, seven shrub and twenty eight herb species were found in the lower altitude with Pinus wallichiana as dominant tree species. The mid altitude had species richness of 07 tree species, 06 shrub and 25 herb species. The Shannon diversity index showed a decreasing trend from lower altitude to higher one in all three life forms. The distribution and species richness pattern of different species are affected by various locality factors and can be used for managerial aspects. Hence the present study can form a baseline for implementing management aspects for conservation, regeneration strategies and application of silvicultural systems at different altitudes and species wise.